Research on the Design Strategy of Adaptive Urban Waterfront Parks Based on Rainwater Resilience: Taking the Waterfront Space Near Hongdao Street in Qingdao As an Examples - Zhou, Zehui (International Journal of Natural Resources and Environmental Studies, 2025)
With the acceleration of urbanization and people’s pursuit of healthy lifestyles, the development and utilization of urban waterfront space has become more and more important, and ecological parks have also received more and more attention and attention. The research target of this article is the waterfront space located in Hongdao Street, Chengyang District, Qingdao City, Shandong Province, China. Based on the perspective of waterfront park transformation, the concept of "resilient landscape" is introduced to explore the design and implementation of sports ecological parks in urban waterfront spaces. Construction, in order to provide a multi-functional, sustainable public space to meet people’s comprehensive fitness and leisure entertainment needs. The core issue is how to realize the comprehensive utilization and ecological restoration of waterfront space through river reconstruction and the design of sports ecological parks, so as to create a healthy and beautiful urban living space for people. It provides a reference for the construction of sponge cities in Qingdao and is of great significance to the construction of sponge cities and ecological civilization.